Nitrogen reduction effect of side-deep placement of fertilizer on the rice production - HUAI Yan; CHEN Zhaoming; ZHANG Gengmiao; JIANG Mingbei; XU Jianfeng; WANG Qiang (浙江大学学报. 农业与生命科学版, 2020)
A field experiment was conducted to assess the effects of side-deep placement of fertilizer on the rice (early rice and single cropping late rice) yield, apparent nitrogen use efficiency (ANUE) and ammonia volatilization (AV). Five treatments were conducted: 1) no nitrogen fertilizer (N0); 2) conventional fertilizer (CF); 3) side-deep placement of compound fertilizers (90%CFD); 4) broadcast application of slow-release fertilizer (80%CRF); 5) side-deep placement of slow-release fertilizer (80%CRFD). Results showed that the 90%CFD, 80%CRF and 80%CRFD reduced application rate of N fertilizer by 10% and 20%, but could maintain the grain yields of early rice and single cropping late rice as compared with the CF. The grain yield of single cropping late rice was significantly higher in the 80%CRFD than in the 80%CRF. The AV amounts ranged from 12.45 to 18.50 kg/hm2 and 18.75 to 26.23 kg/hm2 in the three treatments (90%CFD, 80%CRF and 80%CRFD) during the growth period of early rice and single cropping late rice, respectively, and all of those were significantly lower as compared with the CF treatment. The AV rates in the 90%CFD, 80%CRF and 80%CRFD treatments were 9.3%-12.6% and 10.4%-12.9% during the growth period of early rice and single cropping late rice, respectively. Compared with the CF, the three treatments (90%CFD, 80%CRF and 80%CRFD) decreased the AV rates by 2.0-5.3 and 2.4-4.9 percentage points in the early rice and single cropping late rice, respectively. The AV rate was lower in the 80%CRFD than in the 80%CRF in both of the early rice and single cropping late rice. The ANUEs in the three treatments (90%CFD, 80%CRF and 80%CRFD) were 35.6%-46.9% in the early rice, and they were 4.0-15.3 percentage points higher than in the CF. In the single cropping late rice, the ANUE increased in the side-deep placement treatments of fertilizer (90%CFD and 80%CRFD) as compared with the CF, but there was no significant differences between the 80%CRF and CF treatments. It is concluded that the 90%CFD, 80%CRF and 80%CRFD are the recommended fertilizer management in the early rice, and the 90%CFD and 80%CRFD are the recommended fertilization patterns in the single cropping late rice.